Social Work and Criminal Justice Student Support of Civil Liberties - Fabianic, David A. (1979)
Varying levels of support for civil liberties have been imputed to social work and criminal justice personnel. Assuming students planning to pursue these professional roles reflect attitudes in accordance with anticipated demands of the positions and the effects of preparatory educational experiences, this paper examines the levels of support for selected provisions of the Bill of Rights among social work and criminal justice undergraduate students